Subtemporal Transtentorial Petrosalapex Approach for Giant Petroclival Meningiomas: Analyzation and Evaluation of the Clinical Application - Yang, Jun; Liu, Yan-Hong; Ma, Shun-Chang; Wei, Lin; Lin, Rui-Sheng; Qi, Jian-Fa; Hu, Ye-Shuai; Yu, Chun-Jiang (Journal of Neurological Surgery Part B: Skull Base, 2012)
With the advent of microsurgery and surgical techniques, along with the improvement in neuroimaging techniques and the microanatomy in cadaver study, improvement in terms of surgical morbidity and mortality has been remarkable; however, controversy still exists regarding the optimal surgical strategies for giant petroclival meningiomas (GPMs). We report a study of clinical and radiological features as well as the surgical findings and outcomes for patients with GPM treated at our institution over the past 6 years. During a 6-year period (April 2004 to March 2010), 16 patients with GPM underwent surgery by subtemporal transtentorial petrosal apex approach during which electrophysiological monitoring of cranial nerves and brainstem function were reviewed. There were nine females and seven males with a mean age of 56.9 years (range from 32 to 78 years). The most frequent clinical manifestations were headache (93.7%) and dizziness (93.7%). Regions and directions of tumor extension include clivus, parasellar, and cavernous sinus, as well as compression of brainstem, and so on. The trochlear nerve was totally wrapped in nine cases (56.2%). The postoperative Karnofsky Performance Scale (KPS) score was 76.3 ± 13.1. Mean maximum diameter of the tumors on magnetic resonance imaging was 5.23 cm (range, 4.5 to 6.2 cm). Subtemporal transtentorial petrosalapex approach was performed in all 16 cases. Gross total resection was achieved in 14 cases (87.5%) and subtotal resection in 2 cases (12.5%) with no resultant mortality. Follow-up data were available for all 16 patients, with a mean follow-up period of 28.8 months (range from 4 to 69 months), of which 11 (68.75%) lived a normal life (KPS, 80–100). Our suggestion is that GPM could be completely resected by subtemporal transtentorial petrosalapex approach. The surgical strategy of GPM should be focused on survival and postoperative quality of life. Microneurosurgical technique plays a key role in tumor resection and preservation of nerve function. Intraoperative electrophysiological monitoring also contributes dramatically to the preservation of the nerve function. Complete resection of the tumor should be attempted at the first operation. Any remnant is treated by radiosurgery.
Keywords: subtemporal transtentorial petrosalapex approach; petroclival areas; meningioma; surgical approach; electrophysiological monitoring